History of the Transmission of Greek Philosophical Thought into Islamic Philosophical Thought from the Classical Ages to the Middle Ages - Rosyada, Yassirly Amrona (Journal of Islamic History, 2023)
The development of philosophy touched various sciences and also entered religious teachings. Islamic thinkers succeeded in developing science, basing their work on Greek philosophical thought without merely copying it. The distinction regarding the assumption that Islamic philosophy is merely a copy of Greek philosophy, or the existence of an anti-Islamic philosophy stance due to Western philosophical influences, must be clearly clarified. The method used in this research is the literature method, to answer how the history of scientific transmission from Greek philosophy to Islamic thought occurred. The research results show that the transmission of knowledge from Greek philosophy to Islamic thought was carried out through translation movements, the development of thought, and the integration of knowledge. Greek philosophical thought and Islamic philosophical thought have a functional relationship. Greek philosophical thought is synthetic, continuous, and analogical, while Islamic philosophical thought is based on jadalli (dialectical) thinking. Doctrinally, Greek philosophical thought gives freedom to reason as the center of thought, while Islamic philosophical thought seeks knowledge with reason within the realm of religious teachings. In Islamic philosophy, the rationality of thought is used in the istinbat (derivation) of laws, one of which can be seen in the qiyas (analogical deduction) method. Keywords: greek philosophy, islamic philosophy, transmission of knowledge. REFERENCES Ahwani, Ahmad Fuad al, (1985). tt, Filsafat Islam, Jakarta: Pustaka al Firdaus. Ali, Israq, “Tentang Transmisi Filsafat Yunani kepada Para Filsafat Muslim Abad Pertengahan”, ScuELO SA, vol.78 n.4, Juli/2022. Ali, Yunasril, (1991) Perkembangan Pemikiran Falsafi dalam Islam, Jakarta: Bumi Aksara. Al Jabir,i (1991), Takwin al Aql al Arabi, T.tp: Markaz al Tsaqafi al Arabi. Edwards (ed), Paul, (1976), The Encyclopedia of Philosophy, New York: The Mac Millan Publishing co. Effendi, Satria, (2005), Ushul Fiqh, Jakarta:Kencana. Fakhry, Madjid, (1983), a History of islamic Philosophy, New York: Colombia University Press. Gazalba, Sidi, (1992), Sistematika Filsafat I, Jakarta: Bulan Bintang. Ghufron, Mohammad dan Rahmawati, (2013), Ulumul Hadis Praktis dan Mudah, Yogyakarta: Teras. Hasymi, (1975), Sejarah Kebudayaan Islam, Jakarta: Bulan Bintang. Hatta Mohammad, (1952), Alam Pikiran Yunani, Jakarta: Tinta Mas. Hitti, Philip K., (1986), History of the Arabs, New York: Martin Press. Ibn Rusyd, tt, al-Kasyf ‘an Manahij al-Adillah, Mesir: Dar al-Majmu’ al-Maktabah al-Mahmudiyah, (1986), Tahafut at-Tahafut, Beirut: dar al-Masyriq. Maqsud, Abdul Maqsud Abdul Ghani Abdul, (2000), Agama dan Filsafat, alih bahasa Saifullah dan Ahmad Faruq, Yogyakarta: Pustaka Pelajar. Nasution, Harun, 1986, Akal dan Wahyu, Jakarta: UI Press. (1973), Filsafat dan Misticisme dalam Islam, Jakarta: Bulan Bintang. Nasution, Hasyimsyah, (1999), Filsafat Islam, Jakarta: Gaya Media Pratama. Poedjawijatna, I.R., (1974), Pembimbing ke Arah alam Filsafat, Jakarta: Pembangunan. Poerwadarminta, W.J.S., (1976), Kamus Umum Bahasa Indonesia, Jakarta: Balai Pustaka. Soleh, Khudori, (2014), Filsafat Islam Dari Klasik Hingga Kontemporer, Yogyakarta: ar Ruzz Media. Sukri, (2023), Transmisi Filsafat Aristoteles Terhadap Filsafat Islam, Medan: Perdana Publishing. Supriyadi, Dedi, (2009), Pengantar Filsafat Islam Konsep, Filsuf, dan Ajarannya, Bandung: Pustaka Setia. Waridah, Ernawati, (2017), Kamus Bahasa Indonesia, Jakarta: Bmedia. Zainun Kamal, (2006), Ibn Taimiyah Versus Para Filosof Polemik Logika, Jakarta: Raja Grafindo Persada.